Halide Perovskites: Interfaces Between Graphene‐Related Materials and MAPbI3: Insights from First‐Principles (Adv. Mater. Interfaces 22/2018). Issue 22 (22nd November 2018) - Volonakis, George; Giustino, Feliciano
Abstract : Atomistic model of the interface between the prototype photovoltaic perovskite material CH3 NH3 PbI3 and a monolayer of graphene. Within article number1800496, George Volonakis and Feliciano Giustino present the latest advances on the computational exploration of the interactions between graphene and graphene oxide with lead halide perovskites. They also show how recent calculations from first principles have been employed towards understanding the benefits of combining these 'wonder materials'.